The need for legal protection of mental disorder patients in Malaysia / Nur Zatil Aqma Zoal Azha … [et al.] - Zoal Azha, Nur Zatil Aqma; Pakri, Mohamad Hafiz; Hashim, Nur Atikah; Ridzwan, Nurul Amirah (2010)
This legal research is conducted with an aim to study and analyse the protection of mentally disordered patient from being ill-treated by irresponsible parties. Though, there are legislation provided such as the Mental Health act 2001 and the Federal Constitution in protecting such right, it is however lacking in many ways. Thus, this research will focus on the protection of the mentally disordered person in protecting their rights and liberties which is lacking in our jurisdiction. The scope of this legal research is on the legislation on mentally disordered patients. Besides that a comparative analysis study has been made with Singapore, India, Hong Kong and England. This legal research will be based on the secondary sources from the Law Library of Universiti Teknologi (UiTM). Legislation, newspaper articles, cases, and other appropriate sources that relates to mental disorder patient are also used. It is hoped that this legal research will provide a comprehensive discussion on the rights of mental disorder patient in Malaysia and proposed amendments or suggestion to the current laws to give protection to the mentally disorder patient.